2013
DOI: 10.3174/ajnr.a3650
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings of Head and Neck Dermatofibrosarcoma Protuberans

Abstract: BACKGROUND AND PURPOSE:Dermatofibrosarcoma protuberans is a rare, locally aggressive sarcoma of the skin in children and adults, usually involving the trunk and extremities and less commonly the head and neck. Despite clinical reports in the literature on the management of dermatofibrosarcoma protuberans, there are limited articles describing its imaging features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…On T1-weighted imaging, the tumor was isointense, slightly hypointense or hyperintense compared with that in skeletal muscle. In a review by Millare et al (12), all 14 MRI T1-imaged lesions were demonstrated to be isointense compared with those in muscle tissue. In a study by Jiang et al (2), targeted ultrasound of the breast revealed a hypoechoic mass lesion with irregular borders and no peripheral or internal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…On T1-weighted imaging, the tumor was isointense, slightly hypointense or hyperintense compared with that in skeletal muscle. In a review by Millare et al (12), all 14 MRI T1-imaged lesions were demonstrated to be isointense compared with those in muscle tissue. In a study by Jiang et al (2), targeted ultrasound of the breast revealed a hypoechoic mass lesion with irregular borders and no peripheral or internal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatofibroma, whether single or multiple, occurs in various parts of the limbs, accompanied by thickening of the skin tissue. 3 Neurogenic tumors include schwannomas and neurofibromas, which grow mainly along nerves. Schwannoma often shows cystic degeneration heterogeneous enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…DFSP is often superficial; therefore, there are few reports focusing on imaging findings of DFSP. 3 12 Herein, we provide a retrospective review of the imaging findings of 27 cases of DFSP with the aim to improve our knowledge of DFSP.…”
mentioning
confidence: 99%
“…On magnetic resonance imaging, DFSP is homogeneous and iso- or hypo-intense to muscle. They are strongly enhanced post-contrast on T2-weighted images [9].…”
Section: Discussionmentioning
confidence: 99%